The effect of stress on distance learning nursing degree students: a cross-sectional study / Rosuzeita Fauzi ... [et al.] - Fauzi, Rosuzeita; Mazlan, Muhamad Fauzi; A Rahman, Muhammad Ariff; Ahmad Sharoni, Siti Khuzaimah; Isa, Roslinda (2021)
Nursing is acknowledged to be a stressful profession worldwide. Being a nurse and a student at the same time is a considerable challenge. Many part-time students experienced stress as they complete their studies. This study aims to investigate the level of stress among e-PJJ nursing degree students. It also seeks to identify the causes and effects of stress on the students. This study applied a quantitative cross-sectional study design. Purposive sampling was used to select the target population of 96 e-PJJ nursing degree students at UiTM Selangor, Puncak Alam campus. The participants included all nursing degree students who were enrolled in a flexible learning course. This study was conducted between January 2019 and January 2020. The study showed most of the respondents had mild stress to severe stress. Headache was identified as the most common effect of stress, while the less common effect is drastic weight loss. Two significant academic factors, feeling stressed as the submission deadline neared and sitting for the examination, were the most influential in causing stress. The one-way ANOVA found statistical differences between the number of children and the stress level. A Tukey post hoc test revealed that those with two children have a significantly higher level of stress, followed by those with one child and those with four children. In conclusion, this study found that most e-PJJ nursing degree students experienced stress, mainly at a low level. Well-managed stress is essential in ensuring part-time students can succeed both in their work and studies.